Concentrated Electrolytes Widen the Operating Temperature Range of Lithium‐Ion Batteries. Issue 18 (23rd July 2021) - Wang, Jianhui; Zheng, Qifeng; Fang, Mingming; Ko, Seongjae; Yamada, Yuki; Yamada, Atsuo
Abstract: The operating temperatures of commercial lithium‐ion batteries (LIBs) are generally restricted to a narrow range of −20 to 55 °C because the electrolyte is composed of highly volatile and flammable organic solvents and thermally unstable salts. Herein, the use of concentrated electrolytes is proposed to widen the operating temperature to −20 to 100 °C. It is demonstrated that a 4.0 mol L −1 LiN(SO2 F)2 /dimethyl carbonate electrolyte enables the stable charge–discharge cycling of a graphite anode and a high‐capacity LiNi0.6 Co0.2 Mn0.2 O2 cathode and the corresponding full cell in a wide temperature range from −20 to 100 °C owing to the highly thermal stable solvation structure of the concentrated electrolyte together with the robust and Li + ‐conductive passivation interphase it offered that alleviate various challenges at high temperatures. This work demonstrates the potential for the development of safe LIBs without the need for bulky and heavy thermal management systems, thus significantly increasing the overall energy density. Abstract : Owing to the highly stable solvation structure, concentrated electrolyte enables the stable operation of LiNi0.6 Co0.2 Mn0.2 O2 |graphite full cells in a wide temperature range from −20 to 100 °C, which alleviates various challenges faced by commercial dilute electrolytes. This study demonstrates the potential to build a safe battery system without the bulky and heavy thermal management system, thus significantly increasing the overall energy density.